CONTRASTIVE ANALYSIS OF TENSE AND ASPECT ON SHUNKAN DOUSHI IN BAHASA AND JAPANESE - Nita Rustanti (Faculty of Economics, Law, and Humanities, 2019)
Tense and aspect are one of the most important part on languange grammar. It used on everyday conversation so understanding it are a must for foreign languange learners, but it can be difficult to them because not all of languange have tense and aspect. This study aims to describe similarities and differences of tense and aspect on shunkan doushi in Bahasa and Japanese. This study uses a contrastive analysis method by taking data from various sources. The result of this study are 1) the similarities between them are temporary adverbial can be used in both of languange. Meanwhile, the differences between them are 2) there is changes on the verb in Japanese meanwhile, in Bahasa there is no changes. 3) In this study, tenses on Japanese shunkan doushi, it can be used only for past tense and future tense, meanwhile in Bahasa it can be used on past tense, simple tense and future tense, 4) in this study, all of the aspect on Japanese are kigentai which mean an ending, meanwhile in Bahasa it can be an ending, progressive, continuative or repetitive.